PRICE INTEGRATION IN RICE SURPLUS AREA IN INDONESIA - Oktarina, Yetty (INFOKUM, 2022)
Price integration in rice surplus areas in Indonesia. The purpose of this study is to analyze the integration of traditional markets that occur in rice commodities that are traded in Indonesia's surplus areas. The data used in the study are time series from 2018-2020, the price of rice in five regions: East Java, Central Java, West Java, South Sulawesi and South Sumatra. Data analysis using E-views 11. The findings of this study are that it can be concluded that the integration of rice prices between regions with rice surpluses will help other regions with rice deficits. Inter-regional markets will occur and create stable price opportunities. Farmers who become producers will get a fixed market to market rice. The government policy regarding the basic price of rice can also be implemented, by seeing that all producers (farmers) and consumers are not disadvantaged.